Assessment Of Trend And Instability Of Area And Production Of Mung Bean In Bangladesh - Prioty, JK; Rahman, KS; Miah, MAM (SAARC Journal of Agriculture, 2024)
Instability is an inherent aspect of agriculture due to its reliance on weather conditions, resulting in substantial fluctuations in crop area, production and yield. Mung bean (Vigna radiata) is one of Bangladesh’s most important pulses. It is highly valued for its nutritional composition and also helps improve soil health. This study focused on analyzing the changes in the cultivation area, production and yield of mung bean in Bangladesh through growth rate and instability analysis based on secondary data over a 40-year period (1981-2020). The entire timeframe was divided into four sub-periods:1981-1990,1991-2000,2001-2010 and 2011-2020 allowing for analysis using various statistical tools. Growth rates were calculated by fitting an exponential growth function, while instability was assessed using the Cuddy-Della Valle index. The analysis revealed that the area and production of mung beans had increased. The change in area and yield contributed respectively 51.3% and 46.8% to changes in the mean production of mung bean at the national level. Though the mung bean yields increased significantly, the rate of growth is slow, and it is insufficient to meet our country's demand. The analysis also revealed that the area, production, and yield of mung bean were not stable during the study period. SAARC J. Agric., 22(1): 181-189 (2024)